An Epidemiological Study of Diabetes Mellitus in Productive Aged Urban Nepalese of Makalbari Area of Gokarneshwor Municipality (Nepal Medical College Journal, 2020)
Diabetes mellitus is a chronic disease that through its complications can seriously impact the quality of life of an individual. The incidence of diabetes mellitus is starting to rise at a younger age. This study is carried out to determine the prevalence of diagnosed diabetes mellitus in productive aged persons and to study the association of socio-demographic characteristics, body mass index (BMI) and blood pressure among persons with and without diabetes mellitus. A community-based cross-sectional, observational study was conducted in Makalbari area. Systematic random sampling technique was used to select the households. The family members from those households who met the inclusion criteria were interviewed with self-constructed semi-structured questionnaire which included socio-demographic information of respondents. Height, weight and blood pressure were recorded. BMI was interpreted as per WHO guidelines and hypertension was defined as per Joint National Committee (JNC) VII guidelines. Among total 662 participants, 342 (51.7%) were female and 320 (48.3%) were male. About 196 (29.6%) of subjects were between 25 to 34 age group followed by 145(21.9%) of them in 35 to 44 age group. Prevalence of diagnosed diabetes mellitus in productive aged persons in urban area was 3.8%. The prevalence of BMI of ≥25 was 42.4%. Out of total subjects, maximum number of respondents were prehypertensive 406 (61.3%). Mean age of total participants was 37.9±13.59 and BMI was 24.15±3.89.The age of respondents was highly statistically significant among the persons with diabetes (p = 0.000). The number of diabetes mellitus increased with increase in age and BMI of the participants. Prevalence of diabetes mellitus was almost same in both male 13 (52.0%) and female 12 (48.0%). Diabetes mellitus was seen more in subjects who had completed secondary level education 11 (44.0%) and in homemakers and government job holders, 3 (33.3%) each. In conclusion, most of the people in productive age groups were preobese and were in prehypertensive stage which may increase the risk of acquiring diabetes mellitus in future. This necessitates the screening of more persons in productive age group for diabetes mellitus.